Political Economy of Regional Peacebuilding and Politics of Funding - (:unkn) unknown (My University, 2024)
This article examines the political economy of regional peacebuilding programmes in the era of diminishing funding. Employing methodology of qualitative text analysis and interpretation the article analyses the politics of funding regional peacebuilding. One of the central problems of peacebuilding in Africa is its dependence on external funding. Donor, bilateral and multilateral actors and agencies fund almost all the peacebuilding processes on the continent. When Western powers divert funding to other part of the world, African peacebuilding faces veritable challenges. This dependence on external financing is increasingly subjected to scathing criticism. Post-Cold War peacebuilding involves two sets of actors: those who provide the finance and those who supply the manpower. However, the informal arrangement where regional economic communities (RECs) provide the troops, while donors and rich countries supply the funding is proving untenable. Some of the questions that the article addresses are: Why is funding for peacebuilding dwindling? Why are some peacebuilding efforts well-funded, while others are not? How is the political economy of funding peacebuilding regulated? How should the AU respond to the diminishing funds? The article argues mobilising own resources could be the way out for Africa in dealing with the convoluted and festering conflicts. It concludes the politics of funding regional peacebuilding is dictated by geostrategic interests and short-term calculations rendering it unpredictable, unsustainable and ineffective.
Keywords: African Research